Design of Fresh Vegetable Quality Monitoring System Based on the Internet of Things (IoT) - Amri, Syahputra; Bukhori, Alan Akbar; Zahro, Annisa; Pasaribu, Filemon Agustinus; Fragastia, Vidi Agung (LPPM Universitas Potensi Utama, 2024)
In the fresh vegetable distribution industry, maintaining product quality during transportation is a significant challenge, especially since vegetables are vulnerable to changes in temperature, humidity, and vibrations. This research developed an Internet of Things (IoT)-based vegetable quality monitoring system that utilizes sensors to measure temperature, humidity, vibrations, and GPS location during the distribution process. The system was designed using the Software Development Life Cycle (SDLC) method, which includes stages of analysis, design, development, testing, and maintenance. The monitoring tools consist of the GPS Neo 6m sensor, temperature and humidity sensor (DHT11), vibration sensor (SW-420), as well as the Node MCU ESP32 microcontroller and GSM SIM800L V2 modem. Data was collected during the distribution from Berastagi, Karo Regency, to Pusat Pasar Medan. The monitoring results showed a lowest temperature of 23.6°C and a highest humidity of 93% RH, which are within the safe range. The detected vibration was 94.22%, indicating a low vibration level, which did not cause mechanical damage to the vegetables. Therefore, this monitoring system is effective in maintaining vegetable quality during distribution, and the data obtained validates that transportation conditions did not negatively impact the horticultural products.